LOCAL WISDOM VALUES OF MALAQBI AS THE FORMATION OF MANDAR ETHNIC CHARACTER - Nasir, Muhammad; Danial, Muhammad; Azis, Ahmad Ridhai; Adawiah, Rabiatul (Al-Qalam, 2024)
This research aims to describe the value of local wisdom "malaqbi" in shaping the characteristics and uncovering the factors underlying the existence of the Mandar ethnic group. The study employs a qualitative method with an ethnographic approach (phenomenology, sociocultural, and critical literacy). The research locations are in Napo Village, Limboro District, Polewali Mandar Regency, and Adolang Village, Pamboang District, Majene Regency. Data collection techniques include observation, interviews, FGD (Focus Group Discussion), and documentary studies.The findings indicate the value of local wisdom "malaqbi" in shaping the character of the Mandar Ethnicity, namely: (1) The malaqbi value is used as the basic concept of self-awareness in interpreting the philosophy of Mandar Ethnic life; (2) The malaqbi value is used as the foundation of discourse; (3) The local wisdom value of malaqbi is used as the foundation of attitude; and (4) The malaqbi value is used as the foundation of social behavior. The factors underlying the existence of the local wisdom value of malaqbi in the Mandar Ethnicity are: (1) Awareness of mutual respect and respect for fellow human beings; (2) Awareness of clarifying identity as Mandar people; (3) Awareness of historical events; and (4) Awareness of "siri'" as the consequence of behavior that is not in accordance with malaqbi.The implication of this research is that the value of malaqbi, which is very wise and full of teachings about life, especially social life, should always be applied by the Mandar Ethnic community in all fields. The malaqbi value has existed before Islamic teachings spread to the Mandar region. Understanding of the malaqbi value even applies to several designations for the Mandar Ethnic community, such as "to I Mandar" (original Mandar people), "to Mandar" (people who come and reside in Mandar), and "pammandar" (people who come to Mandar for specific purposes but do not reside there or only temporarily).